Bacteriological Analysis of Water of Kathmandu Valley - Ghimire, Gyanendra; Adhikari, Binita; Pradhan, Manoj (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Water is indispensible for human existence. Water pollution is the most serious environmentalquality issue all over the world, yet the people are less aware and give little emphasis on the vital connectionbetween water and health. Drinking water of most communities and municipalities in Nepal is obtained fromsurface sources, rivers, streams, ponds and lakes. Most of these sources of water are likely to pollute withdomestic and industrial wastes and many types of microorganisms present in water causes various types ofinfectious diseases. Therefore, we intend to Þ nd the bacteriological water quality of Kathmandu valley. Methods: A total of 200 water samples collected from different sources (over head tank, well and tube wells,taps, springs through spouts and household Þ lter) from different parts of Kathmandu Valley were subjected forbacteriological analysis by MPN (3 sets 3 tubes) method. Presence of fecal coliform was detected by Eijkmantest. Result: Out of total 200 water samples, 130 (65.0%) were unsatisfactory, 19 (9.5%) were intermediate(suspicious), 30 (15.0%) were satisfactory and remaining 21(10.5%) were excellent. Of the unsatisfactorywater samples subjected to Eijkman test, 22.0% of overhead tank, 30.0% of ground water, 30.0% of pipedtap water, 40.0% of natural tap (spout) and none of the household Þ lter water showed fecal coliforms. Watercontamination rate was higher during summer than in winter season. Conclusion: It is concluded that most of the water sources of Kathmandu valley are bacteriologicallyunsatisfactory for drinking. doi: http://dx.doi.org/10.3126/mjsbh.v12i2.12919